Isolation and Characterization of Phosphate Solubilizing Fungus in Vitro (Journal of Nuclear Technology in Applied Science, 2024)
Series of laboratory (in vitro) examinations were carried out to recognizethe most potent fungi isolates and optimum culture conditions helps in solubilizing sparing phosphate in soil. Therefore, the present study aimed to isolate and screening of phosphate solubilizing fungi (PSF), study the contribution of PSF on solubilization of tri-calcium phosphate through excretion of acid and alkaline phosphatase and determine the optimal conditions for phosphate solubilization. From 12 fungal isolates, only four were chosen depending on their capacity to convert tri-calcium – P into soluble one. In this regard, Aspergillus niger, Aspergillus flavus, Aspergillus ficuum and Fusarium oxysporum were efficient in producing halo zone around the colonies on petri dish. Aspergillus niger was the most efficient phosphate solubilizer on Pikovskaya’s agar plates (PVK) achieving solubilization index (PSI) 2.4, followed by Aspergillus flavus with a SI= 2.3. The perfect activities of selected fungal isolates were detected with incubation periods 7 days and temperature 30°C for maximumphosphate solubilization, acid and alkaline phosphatase activities, pH 7.0 for maximum phosphate solubilization, pH 6.0 for maximum acid phosphatase activity while pH 8.0 was suitable for maximum alkaline phosphatase activity for both A. niger and A.flavus.
Keywords: phosphate solubilization; Tri-Calcium Phosphate; P – Ase Enzyme; P-Solubilizing Fungi (PSF)